Low-voltage low-power design and implementation of current-mode circuits - Çakır, Cem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
Low-voltage and low-power analog and digital circuits are needed to realize batteryoptimized, reliable and low-cost electronic devices for many applications. Example applications include remote environmental monitoring, medical diagnostics and consumer products. The need for design techniques to allow circuits to maintain an acceptable level of performance when the supply voltages are decreased is immense. This work is focused on the issues associated with the novel design techniques of current-mode circuits for the applications which require low-power consumption. Firstly, different types of building blocks suitable for low-voltage and low-power operation are proposed, designed and simulated. Then, these building blocks are used to implement current-mode active elements such as current differencing buffered amplifiers (CDBA), operational transresistance amplifiers (OTRA) and current differencing transconductance amplifiers (CDTA). Finally, various analog filters are designed by using the proposed active elements in order to demonstrate the efficiency and usefulness of the proposed circuits. HSPICE tool along with UMC 0.18 μm twin-well CMOS technology is used in this work for schematic capture, simulation and measuring the noise performance. The proposed circuits are translated to their corresponding layouts using Cadence Virtuoso Layout Editor.
Keywords: Metal oxide semiconductor field-effect transistors.; Integrated circuits.